OPTN/SRTR 2016 Annual Data Report: Heart. (2nd January 2018) - Colvin, M.; Smith, J. M.; Hadley, N.; Skeans, M. A.; Carrico, R.; Uccellini, K.; Lehman, R.; Robinson, A.; Israni, A. K.; Snyder, J. J.; Kasiske, B. L.
Abstract: In 2016, 3209 heart transplants were performed in the United States. New, active listings increased 57% since 2005. The number of adult heart transplant survivors continued to increase, and in 2016, 30, 622 recipients were living with heart transplants. Patient mortality following transplant has declined. The number of pediatric candidates and transplants performed also increased. New listings for pediatric heart transplants increased from 454 in 2005 to 624 in 2016. The number of pediatric heart transplants performed each year increased from 319 in 2005 to 445 in 2016. Among pediatric patients who underwent transplant in 2015, death occurred in 5.9% at 6 months and 7.2% at 1 year.